2012
DOI: 10.1111/j.1530-0277.2012.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Cytokine Signaling Pathway Genes in Peripheral Blood Cells of Alcohol Dependent Subjects: Preliminary Findings

Abstract: Background Pre-clinical and clinical studies have implicated changes in cytokine and innate immune gene-expression in both the development of and end-organ damage resulting from alcohol dependence. However, these changes have not been systematically assessed on the basis of alcohol consumption in human subjects. Methods Illumina Sentrix Beadchip (Human-6v2) microarrays were used to measure levels of gene-expression in peripheral blood in 3 groups of subjects: those with alcohol dependence (AD, n=12), heavy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…However, little, if any, information is available regarding how such changes may influence drinking behavior in human subjects. In a previous study, we demonstrated alterations in the expression of multiple stress-related genes in the peripheral blood of subjects with alcohol dependence compared to either heavy or moderate drinkers (Beech et al, 2012). However, since gene-expression was analyzed at only a single time-point, we were unable to determine the relationship of these changes to drinking behavior.…”
Section: Introductionmentioning
confidence: 91%
“…However, little, if any, information is available regarding how such changes may influence drinking behavior in human subjects. In a previous study, we demonstrated alterations in the expression of multiple stress-related genes in the peripheral blood of subjects with alcohol dependence compared to either heavy or moderate drinkers (Beech et al, 2012). However, since gene-expression was analyzed at only a single time-point, we were unable to determine the relationship of these changes to drinking behavior.…”
Section: Introductionmentioning
confidence: 91%
“…Alcohol-induced alterations in gene expression involved in cytokine signaling pathways were examined in male and female subjects with alcohol dependence (AD; more than 25 drinks/week prior to study; n=10), heavy drinkers (HD; defined as regular alcohol use over the past year of at least 8 drinks/week for women and at least 15 drinks/week for me; n=13), and moderate drinkers (MD; defined as up to 7 drinks/week for women and 14 drinks/week for men; n=17). After normalization, 436 differentially expressed genes in blood samples were identified: 291 genes differed between AD and MD subjects, 240 between AD and HD subjects, but only 6 differed between HD and MD subjects (Beech, Qu et al 2012). Many of the differentially expressed genes were involved in the regulation of the immune response by cytokine signaling and the Janus kinase/signal transducers and activators of transcription (JAK-STAT) pathway.…”
Section: Molecular Mechanisms Of Dose Dependent Modulation Of Immunitymentioning
confidence: 99%
“…Many of the differentially expressed genes were involved in the regulation of the immune response by cytokine signaling and the Janus kinase/signal transducers and activators of transcription (JAK-STAT) pathway. Expression of interferon receptor 2 (IFNAR2) was down-regulated in HD subjects compared to MD subjects which could contribute to deficits in both innate and adaptive immunity (Beech, Qu et al 2012). IL-15, a cytokine critical for promoting survival, proliferation, and activation of NK and CD8 T cells, was found to be up-regulated in AD subjects but there was no difference between HD and MD subjects (Beech, Qu et al 2012).…”
Section: Molecular Mechanisms Of Dose Dependent Modulation Of Immunitymentioning
confidence: 99%
See 2 more Smart Citations